Educational Communication from a Historical Perspective and Its Implications for Educational Science - Ahmad Haidar Ali; Tika Faridatul Fitriyah; Khoridatul Azizah (SINGOSARI, 2026)
Communication plays a fundamental role in the development of educational knowledge, not merely as a means of transmitting information but as a process of constructing meaning within the broader context of educational theory. This study aims to examine educational communication from a historical perspective and to analyze its implications for the development of educational science. Specifically, it explores the conceptual foundations of educational communication, its structural elements, potential barriers, as well as its relational dimensions, including assertive and empathetic communication, and their relevance to contemporary learner characteristics. This research employs a qualitative approach using library research, drawing on various scholarly sources such as academic books, journal articles, and relevant documents. Data are analyzed using content analysis to identify, categorize, and interpret key themes related to the evolution and conceptualization of educational communication. The findings indicate that educational communication has undergone significant transformation from a linear and instructive model to a more dialogical and participatory paradigm. Conceptually, it consists of interconnected elements, including communicator, message, media, receiver, and feedback, which function dynamically within different historical and social contexts. Furthermore, the study reveals that communication barriers are shaped by semantic, cultural, psychological, and structural factors, reflecting the complexity of educational interactions. In addition, assertive and empathetic communication emerge as essential relational dimensions that enrich the theoretical understanding of communication beyond cognitive aspects. In conclusion, educational communication contributes not only to the transmission of knowledge but also to the formation of values, critical thinking, and learner character in contemporary contexts. This study provides a theoretical contribution to the field of education by positioning educational communication as a dynamic, historically grounded, and transformative process within the development of educational science.